Reversible Short‐Circuit Behaviors in Garnet‐Based Solid‐State Batteries. Issue 25 (18th May 2020) - Ping, Weiwei; Wang, Chengwei; Lin, Zhiwei; Hitz, Emily; Yang, Chunpeng; Wang, Howard; Hu, Liangbing
Abstract: Garnet‐based solid‐state electrolytes (SSEs) are attractive for solid‐state lithium metal batteries due to their wide electrochemical window, high conductivity, and excellent stability against lithium metal. However, the risk of short‐circuit encumbers the cycle life and capacity of garnet‐based solid‐state batteries without clear reason or mechanism. Here, reversible short‐circuit behavior in the garnet‐based solid‐state batteries, which differs from the short‐circuit in liquid cells, is reported for the first time. In situ neutron depth profiling is adopted to quantitatively measure Li transport, which helps forecast and confirm the reversible nature of the short‐circuit in garnet‐based batteries. A real‐time Li accumulation monitoring system of NMC//CNT/garnet/Li cell is designed to reveal the Li dendrite formation mechanism. The voltage drops of the CNT monitoring electrode during the charging process indicate the formation of Li dendrites inside the garnet bulk, while the smooth voltage profile during the discharging process demonstrates the disappearance of the short‐circuit. This is the first confirmation of short‐circuit behavior that provides clarification of the Li dendrite formation mechanism in garnet‐based solid‐state batteries, which is shown to be a reversible process caused by the low ionic conductivity and non‐negligible electronic conductivity of garnet SSEs. Abstract : A reversible short‐circuit behavior in garnet‐based solid‐state electrolytes (SSEs) is reported. In situ neutron depth profiling and a real‐time Li accumulation monitoring system are adopted to reveal the Li dendrite formation mechanism. This is the first confirmation of reversible Li dendrite formation mechanism in garnet‐based SSEs, which is attributed to the low ionic conductivity and non‐negligible electronic conductivity of garnet SSEs.